2016
DOI: 10.1007/s00426-016-0828-4
|View full text |Cite
|
Sign up to set email alerts
|

Trial-by-trial switching between procedural and declarative categorization systems

Abstract: Considerable evidence suggests that human category learning recruits multiple memory systems. A popular assumption is that procedural memory is used to form stimulus-to-response mappings, whereas declarative memory is used to form and test explicit rules about category membership. The multiple systems framework has been successful in motivating and accounting for a broad array of empirical observations over the last 20 years. Even so, only a couple of studies have examined how the different categorization syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 42 publications
2
30
2
Order By: Relevance
“…We have previously speculated that system switching may be mediated via the hyperdirect pathway of the basal ganglia (Ashby & Crossley, 2010; Crossley & Ashby, 2015; Crossley et al, in press). The hyperdirect pathway begins with direct excitatory glutamate projections from frontal cortex to the subthalamic nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously speculated that system switching may be mediated via the hyperdirect pathway of the basal ganglia (Ashby & Crossley, 2010; Crossley & Ashby, 2015; Crossley et al, in press). The hyperdirect pathway begins with direct excitatory glutamate projections from frontal cortex to the subthalamic nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Crossley et al ( 2017 ) published a new experiment again using disks with sine-wave gratings but this time adding back the background color cue and separate response buttons (4 categories) used in Erickson ( 2008 ). Crossley et al used more training trials, and obtained a proportion of switchers close to 40%, which is higher than Ashby and Crossley ( 2010 ) and close to Erickson ( 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…System-switching would be a special case of task-switching in which each task relies on a different categorization system. To explore this possibility, Crossley et al ( 2017 ) also included a condition in which participants needed to switch between two different declarative strategies. The results showed that the switch cost was smaller when switching within the declarative system compared to switching between a declarative and a procedural system.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it is assumed that there is a bias toward the verbal system, with humans biased to spontaneously form task-sets. Switch costs may reflect the cognitively demanding process of reconfiguring between task-sets (Koch et al, 2018), while category learning also assumes that switching between the categorization systems is subject to interference (Crossley et al, 2018). At what point do these systems differ?…”
Section: Relationship To Category Learningmentioning
confidence: 99%